Effect of Service Quality on Customer Satisfaction at Popeye Chicken Exspress Kleco in Surakarta - Adhita Maharani Dewi (Journal of Research in Business, Economics, and Education, 2020)
The purpose to be achieved in this study is to determine the effect of quality service has an effect on customer satisfaction at Popeye Chicken Express Kleco Branch at Surakarta. In connection with these objectives, the following hypothesis is proposed the effect of quality tangible service, empathy, reliability, certainty, and responsiveness partially and simultaneously to customer satisfaction at Popeye Chicken Express Kleco in Surakarta. Sampling of this method of research using non-probability sampling with the type of non-probability sampling used is purposive sampling. By population and sample used in this study were 100 people, data collection in this study using. The questionnaire and analysis techniques used are validity test, reliability test, classical assumption test and test hypothesis using IBM SPSS Statistics 23. The analysis results show that the tangible service quality variable does not have a positive effect on customer satisfaction with a value of t count 0.043 with sig. 0.966, the service quality variable has no empathy positive effect on customer satisfaction with a value of t count 1.090 and sig. 0.278, variable Service quality reliability has a positive effect on customer satisfaction with a t value of 2.090 and sig. 0.039, the variable quality of service assurance has a positive effect on customer satisfaction with a value of t count 2.427 and sig. 0.017, and the variable responsiveness of service quality has no effect positive on customer satisfaction with a value of t count 1.290 and sig. 0.200.